Measuring conditional persistence in time series - George Kapetanios (Queen Mary University of London, Department of Economics, 2002)
The persistence properties of economic time series has been a primary object of investigation in a variety of guises since the early days of econometrics. This paper suggests investigating the persistence of processes conditioning on their history. In particular we suggest that examining the derivatives of the conditional expectation of a variable with respect to its lags maybe a useful indicator of the variation in persistence with respect to its past history. We discuss in detail the implementation of the measure. We present a Monte Carlo investigation of the suggested measure. We further apply the persistence analysis to real exchange rates.
Keywords: C22; C14; F31; 330; Persistence; Nonparametric regression; Nonlinear models; Real exchange rates; Zeitreihenanalyse; Nichtparametrisches Verfahren; Regression; Kaufkraftparit\~AƒÂt; Messung